2015
DOI: 10.17576/jsm-2015-4403-15
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Gaseous BTEX Adsorption on RH-MCM-41 by Chlorosilanes

Abstract: In this research, the surface hydrophobicity of a mesoporous molecular sieve synthesized from rice husk silica, called

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Understanding adsorption of VOCs can help with designing materials for separation, and a recent study showed the potential of silica as a separation material for VOC mixtures using dynamic adsorption. , Moreover, most studies provide the adsorption capacity for VOCs but not the kinetics. , Understanding the temperature-dependent surface dynamics of nanoporous silica materials requires further study. The literature also lacks information about the equilibrium and sorption kinetics at different temperatures, which is expected to be adsorbate/adsorbent-dependent, as well as studies of sequential adsorption of VOCs onto porous materials.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding adsorption of VOCs can help with designing materials for separation, and a recent study showed the potential of silica as a separation material for VOC mixtures using dynamic adsorption. , Moreover, most studies provide the adsorption capacity for VOCs but not the kinetics. , Understanding the temperature-dependent surface dynamics of nanoporous silica materials requires further study. The literature also lacks information about the equilibrium and sorption kinetics at different temperatures, which is expected to be adsorbate/adsorbent-dependent, as well as studies of sequential adsorption of VOCs onto porous materials.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed the efficiency of non-thermal plasma catalysis (Guo et al 2006), condensation, membrane separation, biofiltration (Quoc An et al 2011;Zhao et al 2011), adsorption (Areerob et al 2015;Yakout & Daifullah 2014;Yang et al 2013), photocatalysis (Luo et al 2006;Momani & Jarrah 2009) and catalytic oxidation (Jothiramalingam & Wang 2007;Santos et al 2010) in the decomposition of VOCs present in the atmosphere. Though some processes are found to be effective, the ease of performing the process and the means of producing its precursors must also be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%